2011
DOI: 10.1016/j.pain.2010.11.012
|View full text |Cite
|
Sign up to set email alerts
|

On the relationship between nociceptive evoked potentials and intraepidermal nerve fiber density in painful sensory polyneuropathies

Abstract: This study analyzed the relationship between the density of intraepidermal nerve fibers (IENF) and the characteristics of either nociceptive laser-evoked potentials (LEPs) or contact heat-evoked potentials (CHEPs) in patients with painful sensory polyneuropathy with the aim to determine which parameters of LEPs and CHEPs more reliably reflect IENF loss. A total of 96 patients and 35 healthy volunteers took part in the study. Based on clinical examination, nerve conduction tests, and quantitative sensory testin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(75 citation statements)
references
References 40 publications
4
70
0
1
Order By: Relevance
“…36 This is likely for two main reasons: NCS offer a robust and objective means of assessing neuropathy, while WT is a subjective measurement of small fiber function. Cassanova et al 37 in their study found that even patients with no IENFs had consistent responses in WT and concluded that it is possible for partially damaged nerve endings to still generate a propagated action potential. We speculate that a similar association may exist for the corneal subbasal nerves.…”
Section: Discussionmentioning
confidence: 96%
“…36 This is likely for two main reasons: NCS offer a robust and objective means of assessing neuropathy, while WT is a subjective measurement of small fiber function. Cassanova et al 37 in their study found that even patients with no IENFs had consistent responses in WT and concluded that it is possible for partially damaged nerve endings to still generate a propagated action potential. We speculate that a similar association may exist for the corneal subbasal nerves.…”
Section: Discussionmentioning
confidence: 96%
“…Latency and amplitude nociceptive‐evoked potentials are associated with the density of intraepidermal nerve fibers. Nociceptive evoked potentials with skin biopsy may be used in the diagnosis of painful neuropathy (Casanova‐Molla, Grau‐ Junyent, Morales, & Valls‐Solé, 2011). …”
Section: Diagnostic Techniquesmentioning
confidence: 99%
“…However, LEPS may cause skin injuries in laser-stimulated areas, while CHEPS, in addition to being more sensitive and specific, is noninvaise and able to generate reproducible evoked potentials. There is still no standardization for both methods for the clinical practice 61 .…”
Section: Evoked Potentialsmentioning
confidence: 99%